Pengaruh Kualitas, Harga, dan Pelayanan Terhadap Kepuasan Pelanggan di Kedai Itah Tangkiling - Fiore Nopellin; Revnussa Octobery; Dewi Rakhmawati (Edunomics Journal, 2024)
Whether a business survives or not depends on the strategy used by the business owner, where the strategy used to satisfy customer needs is in accordance with what is expected, it would even be better if it exceeds customer expectations. Entrepreneurs in the culinary business must pay attention to changes in the behavior of each consumer, so that the products offered sell well. Understanding consumers is very important because it will become capital for the business in the future to achieve goals, one of which is achieving consumer satisfaction. Based on the title of this research, to find the influence of quality, price and service on customer satisfaction, the method used in this research is quantitative. Data analysis is the process of systematically searching and compiling data obtained from distributing questionnaires. The analytical model used to analyze the influence of Quality and Price variables on Customer Satisfaction is by using the SPSS computer program (software). The approach taken in this research is a quantitative approach that focuses on the influence of quality, price and service on customer satisfaction at Kedai Itah Tangkiling. The type of research used in this research is quantitative research with a descriptive approach. The data analysis techniques in this research are multiple linear regression, F statistical test, individual parameter significance test (T test), and coefficient of determination R2. Based on the description previously explained, it can be concluded that quality, price and service simultaneously influence customer satisfaction. Based on the test results above, it can be seen that the Fcount is 60,829 with the Ftable value being 2.85, so the Fcount > Ftable or 60,829 > 2.85, and the significance level is 0.000 < 0.05. So H1, H2 and H3 are accepted